Islet autotransplantation: past, present and future. Chapter II: the role of islet autotransplantation for the treatment of chronic pancreatitis. (March 2015) - Linetsky, Elina; Sayki Arslan, Muyesser; Alejandro, Rodolfo; Ricordi, Camillo
SUMMARY : The most successful islet transplants have been performed in non-autoimmune diabetes patients, in an autologous setting, in conjunction with total or near-total pancreatectomy for the treatment of pancreatic or hepatobilliary conditions. The primary goals are the treatment of an underlying disease and relief of persistent pain. Islet autotransplantation is important in this setting. Following islet autotransplantation most patients maintain good glycemic control, with ˜30–40% able to discontinue insulin therapy. Transplantation of high islet mass is associated with higher C-peptide, in-range HbA1c and insulin independence. Strategies to increase the proportion of insulin independent patients and long-term engraftment include islet isolation, curtailing the innate immunity-associated events and β-cell apoptosis, and alternative transplant sites. Future studies are of benefit. Chapter II discusses the role of islet autotransplantation in the treatment of chronic pancreatitis.